SADAR PURI UNTUK MENCEGAH DEHIDRASI PADA REMAJA DI SMA NEGERI 5 KOTA JAMBI - Merita Merita; Djayusmantoko Djayusmantoko (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
The reaction in the human body almost requires water. If the body lacks water, it will be associated with dehydration. Therefore, the purpose of this service is to carry out the Self-Urine Check (PURI) counseling in adolescents. This activity was held from May to June 2017, in the SMA 5 Kota Jambi. The target is students of class XI SMA 5 Kota Jambi. This activity consists of giving counseling with power point media, leaflets, posters, and pre-post test questions; practice measuring the scale of hydration using PURI cards and; establishment of a Self-Urine Check. The output of this service activity are: (1) Effective and innovative media / tools / leaflets and modules; (2) Application of conscious PURI and; (3) The formation of a group of mobilizing students aware of PURI. Based on the results of the pre-test it was known that most students did not know that people with more nutritional status were at risk of dehydration (90.9%), and did not know that men were at higher risk of dehydration than women (81.3%). However, after being given counseling all targets can answer post-test questions correctly (100%). Therefore, it is necessary to collaborate with the school with local health agencies in providing health information media and facilities in the school.